ANALYSIS OF EFFECTS OF INSURGENCY ON COWPEA PRODUCTION IN POTISKUM LOCAL GOVERNMENT AREA OF YOBE STATE, NIGERIA - Bawa, A. G.; Sani, M. H.; Iliyasu, Y. (Journal of Agripreneurship and Sustainable Development, 2018)
This study analysed the effects of insurgency on cowpea production in Potiskum local government area of Yobe State, Nigeria. A sample of 120 cowpea farmers were randomly interviewed using structured questionnaire. Data were analyzed using descriptive and inferential statistics. The results show that 35% of the respondents fell within the age bracket of 28-33 years; males constituted 55% and 42% had primary education. The findings further showed that 77.50% of the farmers perceived the effect of insurgency on their livelihood. Majority 70.80% of the respondent perceived increase in poverty and job loses. The result shows that majority (52.5%) of the respondents affected by the conflicts, children (21.7%), women (13.3%) and adult men (8.3%), lost their houses (32.50%), lost their livestock (29.20%), and 16.70% and 13.30% lost their crops and sustained body injury, respectively. Majority (67.50%) of the respondents proffered all the methods in resolving the insurgency, military action (16.70%), negotiation (6.70%), 5.0% and 4.20% suggested state of emergency and amnesty, respectively. Furthermore, regression analysis reveals that 74% variation of the effects of the insurgency on cowpea output was accounted by the independent variables in the model. However, educational level, sex and income were significant at p< 0.001, while household size, farm size and distance from farm to homestead were significant at p< 0.05. Chi-square analysis reveals that the variables included in the model such as sex, educational level, age, income and distance from farmlands to homestead were significant at p< 0.05, with the exception of farm size, marital status and farming experience. The study concluded that insurgency do exist in the study area and the effects include loss of lives, crops, and destruction of infrastructures, such as schools, telecommunication mast, mosques, churches, markets and houses. The study recommended that education and employment opportunities be provided to the youths in the study area.